Highly dynamic and interactive multimedia learning tool for preschool children incorporated with 3D environment / Hoh Yun Yee - Hoh , Yun Yee (2005)
The L TPC System is a standalone application system that promises a quick and efficient way to access information for system users. The L TPC System is build to provide a learning comer for preschool children and as a teaching method for teacher or parent. The L TPC System is to practice children in learning environment by using computer technology. It can eliminate traditional teaching method and children can study in anytime and anywhere, as long as have a computer in hand. The Waterfall Methodology with Prototyping is used to develop the LTPC System. The L TPC System needs special development tools such as Client/Server two tier system architecture, Windows XP Professional as development platform, 3d studio Max 6, Macromedia Flash MX, Adobe Photo hop7.0, Sound Forge 6.0 and Swift 3D.